High species diversity of the genus Neopanorpa (Mecoptera: Panorpidae) in Yunnan Province, China - Wang, Meng; Hua, Bao-Zhen (Zootaxa, 2018)
Neopanorpa van der Weele, 1909 is the second largest genus of Panorpidae, and is endemic to the Oriental Region. Yunnan, a province in the southwestern region of China, is well-known as a biodiversity hotspot and abundant in Neopanorpa species. However, only sixteen species of Neopanorpa have been described from Yunnan hitherto and the taxonomic study of Neopanorpa in Yunnan has lagged far behind as compared with studies performed in neighboring regions. In the present study, notably high diversity of Neopanorpa species is found in the Hengduan Mountains of Yunnan. Seven species of Neopanorpa are described as new: N. semiorbiculata, N. tincta, N. triangulata, N. diancangshanensis, N. magnatitilana, N. longistipitata, and N. quadristigma spp. n. Neopanorpa spatulata Byers, 1965, originally described from Thailand, is recorded from China for the first time. Neopanorpa dimidiata Navás, 1930 is a synonym of N. brisi (Navás, 1930). Keys to species of Neopanorpa in Yunnan are provided. The phylogenetic relationships of Neopanorpa species from the Hengduan Mountains, the Indochinese Peninsula, and the eastern Himalayas are briefly discussed.